Identification of Ferns (Pteridophyta) in the Indrokilo Botanical Garden, Boyolali Regency, as a Resource for High School Biology Learning on Biodiversity - Hidayatun Nurul Khasanah; Agus Purwanto; Anwari Adi Nugroho (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Indonesia is a country with high biodiversity, both flora and fauna. Biodiversity is an important wealth for life and serves as an indicator of the ecological system and a means of detecting changes in species. Identification of ferns (Pteridophyta) was carried out because the Indrokilo Boyolali Botanical Gardens are very supportive for research and have not been clearly identified and used as a source of learning biology. This study aims to identify the types of ferns (Pteridophyta) in Indrokilo Botanical Garden, Kemiri Village, Mojosongo District, Boyolali Regency which is used as a learning resource on Biodiversity material in tenth grade. The method used was exploration research. Data collection is done by exploring, the results are identified using google lens, then used as a learning resource by adjusting the high school syllabus and data analysis using description analysis. The analyzed research report can be used as a learning resource. Research in Indrokilo Boyolali Botanical Garden obtained 31 species of ferns (Pteridophyta) consisting of 14 families namely, Pteridaceae, Polypodiaceae, Dryopteridaceae, Thelypteridaceae, Dennstaedtiaceae, Woodsiaceae, Aspleniaceae, Marattiaceae, Selaginellaceae, Cyatheaceae, Dicksoniaceae, Lygodiaceae, Ophioglossaceae, and Equisetaceae. Through the analysis of the research report, it can be used as a learning resource for high school biology class ten, the material of Biodiversity on KD 3.2 Analyze the various levels of biodiversity in Indonesia. So that the report of the results of this study can be used as additional examples of the level of species-level diversity at the species-level diversity in biodiversity.